Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum Dan Sesudah Akuisisi (Studi Kasus Pada PT. Bank Central Asia Tbk Dan PT. Bank Rakyat Indonesia Tbk) - Dede Hertina; Agnia Novena (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the Comparative Analysis of Financial Performance Before and After the Acquisition at PT. Bank Central Asia and PT. Bank Rakyat Indonesia Tbk which made the acquisition in 2019. This research uses a quantitative approach using secondary data obtained from the official website of each bank. The research variables used in this study consist of Liquidity Ratio (Current Ratio), Probability Ratio (Return on Assets & Return on Equity), Solvency Ratio (Debt to Equity Ratio), Activity Ratio (Total Asset Turnover Ratio). The analytical method used to answer the hypothesis is using the normality test and paired sample T-test. The research results show that there are significant differences in the current assets and return on asset ratio at PT. Bank Central Tbk and PT. Bank Rakyat Indonesia Tbk. Keywords: acquisition, financial performance and financial ratio